PENGARUH PERTUMBUHAN PENJUALAN DAN LIKUIDITAS TERHADAP STRUKTUR MODAL - Sakinah, Gina; Purnama Sari, Yesa Tiara (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
In the business world, competition encourages organizations to increase profitability and value per organization. This is done so that businesses can partner with specialized businesses. The data in this article is secondary data taken from the financial statements of manufacturing companies listed on the Indonesia Stock Exchange, and is supported by literature research and documentation. Based on the results of the study, it can be concluded that partially sales growth does not have a significant effect on the capital structure. Liquidity has no significant effect on the capital structure. Simultaneously, sales and liquidity growth had no effect on the capital structure with a contribution of 35.6% while 64.4% was influenced by other variables that were not studied.